Development of an in-house ELISA for detection of antibodies against Enterococcus cecorum in Pekin ducks. Issue 4 (3rd July 2020) - Jung, Arne; Rautenschlein, Silke
ABSTRACT: Enterococcus cecorum (EC) is known to cause skeletal lesions in broiler chickens and also systemic infections in Pekin ducks. Despite the importance of the pathogen, there is still a lack of serological diagnostic tools for the detection of EC infections. Here we describe the development of an in-house indirect enzyme-linked immunosorbent assay (ELISA) for the detection of EC-specific antibodies and its application by examination of 67 sera from experimentally infected Pekin ducks, 710 field samples from four Pekin duck breeder flocks previously vaccinated with inactivated vaccines, and 80 samples from commercial Pekin ducks coming from vaccinated parent flocks. All groups that had been experimentally inoculated via the air sac route were positive in the new ELISA, with significantly ( P  ≤ 0.05) increased mean sample/positive (S/P) ratios of 0.71–2.70 at days 7, 14 and 21 post-infection, while orally inoculated ducks and the EC-free control group remained negative with mean S/P ratios of 0.0–0.15. Antibodies were also detected in each of four vaccinated Pekin duck breeder flocks; 67.8% of the samples were antibody positive. The highest S/P ratios were found between 16 and 26 weeks (median S/P ratios from 0.15 to 1.03), but antibodies were still detected in some serum samples in weeks 61–67 post-hatch. No antibodies were detected in the commercial Pekin ducks. Antibody development in the ducks may be influenced by the composition of the inactivated vaccine. The new ELISA provides a useful tool for investigations of response to EC infections and vaccinations.